The spatial and temporal abundance of the spider crab Libinia ferreirae Brito Capello, 1871 (Crustacea, Brachyura) considering different environmental factors - Sousa, Aline Nonato de [UNESP] (2021)
The spatial and seasonal distributions of benthic marine organisms are generally linked to the physical and chemical features of the environment. The abundance of Libinia ferreirae Brito Capello, 1871 was analysed in relation to the environmental factors: water temperature (surface and bottom), water salinity (bottom), and substratum (texture and organic matter of the sediment). Samples were collected monthly, from January 1998 to December 1999, in the Ubatumirim (UBM), Ubatuba (UBA) and Mar Virado (MV) Bays, on the northern coast of São Paulo State, Brazil. We caught a total of 213 spider crabs (Ubatumirim = 39; Ubatuba = 53 and Mar Virado = 121). The abundance of L. ferreirae was highest during the spring (October to December) in the three bays. We assume that this result is associated with the entrance of the South Atlantic Central Water during this season, whose features favoured primary productivity and, consequently, displayed a higher food availability for other trophic levels. The lowest number of specimens found during the autumn might be caused by the migration of the population to other sites. The high abundance of L. ferreirae in MV is probably associated with sediment composition, i. e., fine grains which benefit the species’ habit of burrowing in the sediment. Hence, the combination of a favourable sediment homogeneity and the highest food availability seems to be effective modulators of the abundance and distribution of L. ferreira in the bays. This investigation elucidates the importance of analysing environmental factors together, to expand knowledge about the study species.